Pengaruh Jumlah Wisatawan, Jumlah Objek Wisata, Jumlah Restoran, TPK Hotel, dan Investasi terhadap PAD Provinsi Bali - Indina; Hady Sutjipto; Sayifullah (JEMeS - Jurnal Ekonomi Manajemen dan Sosial, 2026)
This study examines the impact of the number of tourists, number of tourist attractions, hotel room occupancy rates, number of restaurants, and investment on Locally-Generated Revenue (PAD) in the regencies and cities of Bali Province between 2015 and 2024. The study employs panel data, combining ten years of time-series data (2015–2024) with cross-sectional data covering nine regencies and cities in Bali. The analysis utilizes panel data regression with a Fixed Effect Model (FEM) approach. The results indicate that the number of tourists, hotel room occupancy rates, number of restaurants, and investment have a significant positive impact on Locally-Generated Revenue. However, the variable representing the number of tourist destinations did not show a significant influence on PAD. Nevertheless, overall, all independent variables—namely the number of tourists, number of tourist attractions, hotel room occupancy rates, number of restaurants, and investment—were found to have a significant impact on Locally-Generated Revenue in Bali's regencies and cities during the study period. These findings demonstrate that progress in the tourism and investment sectors plays a crucial role in strengthening regional financial capacity. Increases in tourist numbers, optimized hotel occupancy rates, growth in the number of restaurants, and rising investment can stimulate economic activity, ultimately leading to an increase in Locally-Generated Revenue.